Combination Of Tea-Ginger-Mint Extract Increase The Elderly Immunity - Darah Ifalahma; Wan Azman Wan Ismail; Isna Dwi Astuti; Anita Dwi Septiarini; Melati Artika Wulansari (Proceeding of International Conference on Science, Health, And Technology, 2021)
During the Covid 19 pandemic it is very important to have an alternative immunostimulant, especially for the elderly who are prone to exposure to the virus. Immunostimulants that are suitable for the elderly are in the form of extracts that can be brewed so that they are comfortable to consume. Many vitamin products and immunostimulant supplements, several important ingredients can be consumed. Some that have good content are tea extract, ginger and mint leaves. The purpose of this study was to determine the effect of the combination of Tea-Ginger-Mint Extract as an immunostimulant on the immunity of the elderly. The study used a Quasy Experimental design with a pretest-posttest non-equivalent control group design. The population of this research is the elderly, the sample of the study is 30 elderly people aged 60-75 years with a purposive sampling technique. The independent variable is the Tea-Ginger-Mint Extract. The dependent variable is the immunity of the elderly. The instrument used is the observation sheet. The treatment was for 4 weeks with the sample divided into 2 groups, namely the control group and the treatment group. Data analysis was carried out in 2 stages, namely Phase I Normality Test and Stage II Influence Test by using T-Test. The experimental results of the treatment group p value 0.00<0.05, which means that there is a significant difference in increasing immunity before and after being given Tea-Ginger-Mint Extract. The results of the T-Test p value 0.000<α0.05, which means that Tea-Ginger-Mint Extract is effective as an immunostimulant to increasing immunity of the elderly. Conclusion the combination of Tea-Ginger-Mint Extract is effective in increasing the immunity of the elderly.